Preharvest Salicylic Acid Application Enhances Pigments, Antioxidants, and Secondary Metabolites in Cannabis sativa L. - N. Montri; C. Tebdoie; Papitchaya Kongchinda; Pornjarus Singhavorachai; Borworn Tontiworachai; Anusorn Cherdthong; C. Yuangklang; R. Deewatthanawong; Sineenart Polyorach (Horticulturae, 2026)
Salicylic acid (SA) is a key signaling molecule regulating secondary metabolism and stress responses in plants, but its preharvest role as a low-cost elicitor in cannabis remains underexplored. This study evaluated the effects of preharvest foliar SA application at different concentrations and application intervals on pigments, antioxidants, and cannabinoids in Cannabis sativa L. leaves and inflorescences. In leaves, moderate SA (0.1 M) significantly enhanced total phenolic content, total flavonoid content, and antioxidant activity (%DPPH inhibition), while higher concentrations suppressed these responses, reflecting a regulated metabolic trade-off rather than irreversible tissue damage. A significant interaction between SA concentration and preharvest time was observed for chlorophyll a (p < 0.01), whereas chlorophyll b and total chlorophyll were not significantly influenced by the interaction. In inflorescences, short-term application of 0.1 M SA (1 h preharvest) maximized phenolics, flavonoids, antioxidant capacity, and pigment accumulation, whereas the untreated controls showed the lowest levels. Cannabinoids exhibited distinct responses: Δ9-tetrahydrocannabinol (Δ9-THC), total tetrahydrocannabinol (Total THC), and tetrahydrocannabinolic acid (THCA) peaked at 0.1 M SA applied 1 h preharvest, while cannabidiol (CBD) was less concentration-dependent, with maximum accumulation observed at 1.0 M SA applied 24 h preharvest. Preharvest SA elicitation strongly modulated cannabis secondary metabolism. Short-term application of moderate SA promoted total phenolic, total flavonoid, antioxidant, pigment, and THC-group cannabinoid accumulation, while CBD displayed broader tolerance to concentration and application timing. These findings highlighted the potential of SA as a preharvest elicitor to improve cannabis phytochemical quality.
Keywords: Cannabis and Cannabinoid Research; Postharvest Quality and Shelf Life Management; GABA and Rice Research